2010
DOI: 10.1007/s10389-010-0369-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of family caregivers—Evidence from Hesse

Abstract: Aim:The aim of the present study is to analyse the health-related quality of life (HRQOL) of primary family caregivers in comparison to the reference values of the average population. Subject and Methods:Data collection took place in the Werra-Meißner district in the year 2009 with a respondent rate of 102 primary family cares of frail elderly people. The health-related quality of life was measured with the Short Form 36 health survey (SF 36) and compared with the German reference values. Results:Compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
0
13
0
2
Order By: Relevance
“…Our results show that the scores in the physical function and social function dimensions are consistent with those in previous studies, and a higher impact on scores resulted from physical and emotional dimensions. Rösler-Shidlack et al 16 evaluated the Qol of family caregivers in a district in Germany and also found lower scores in all the eight dimensions of the SF-36, especially in daily and social activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the scores in the physical function and social function dimensions are consistent with those in previous studies, and a higher impact on scores resulted from physical and emotional dimensions. Rösler-Shidlack et al 16 evaluated the Qol of family caregivers in a district in Germany and also found lower scores in all the eight dimensions of the SF-36, especially in daily and social activities.…”
Section: Discussionmentioning
confidence: 99%
“…Due to care giving, they frequently lack sleep and feel tired and exhausted [ 7 ], and may suffer from anxiety and depression [ 8 ]. Family caregivers, especially in midlife, report lower health-related quality of life than the average population [ 9 ]. Trustful and reliable relationships within their familiar and social systems are important resources for patients in palliative situations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Informal support also tends to differ in terms of location. Co-residential care is more frequent in Southern countries, whilst extra-residential help/care is more common in Northern countries (Hank 2011;Rodrigues et al 2012). Factors such as living arrangements-higher levels of coresidence in Southern countries and a higher number of people living alone in Northern countries-and the lack of formal care services at home in Southern countries can help one explain the differences.…”
Section: Introductionmentioning
confidence: 99%